2019
DOI: 10.1182/blood.2019000790
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated in vivo gene targeting corrects hemostasis in newborn and adult factor IX–knockout mice

Abstract: Many genetic diseases, including hemophilia, require long-term therapeutic effects. Despite the initial success of liver-directed adeno-associated virus (AAV) gene therapy for hemophilia in clinical trials, long-term sustained therapeutic effects have yet to be seen. One explanation for the gradual decline of efficacy over time is that the nonintegrating AAV vector genome could be lost during cell division during hepatocyte turnover, albeit at a slow pace in adults. Readministering the same vector is challengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 30 publications
2
69
0
Order By: Relevance
“…Subsequently, the deletion of Dmd exon 23 with a pathogenic mutation, and the mutation correction in Otc or F9 genes through HDR‐mediated sequence replacement, have been shown to reverse related disease symptoms successfully. More recently, a study reported knock‐in of the hF9 gene using an AAV‐delivered CRISPR system and confirmed the reversal of haemophilia B symptoms in a mouse model …”
Section: High‐efficiency Genome Editing and New Applications Enabled mentioning
confidence: 85%
See 1 more Smart Citation
“…Subsequently, the deletion of Dmd exon 23 with a pathogenic mutation, and the mutation correction in Otc or F9 genes through HDR‐mediated sequence replacement, have been shown to reverse related disease symptoms successfully. More recently, a study reported knock‐in of the hF9 gene using an AAV‐delivered CRISPR system and confirmed the reversal of haemophilia B symptoms in a mouse model …”
Section: High‐efficiency Genome Editing and New Applications Enabled mentioning
confidence: 85%
“…More recently, a study reported knock-in of the hF9 gene using an AAV-delivered CRISPR system and confirmed the reversal of haemophilia B symptoms in a mouse model. 84 Applying CRISPR-Cas9 under ex vivo conditions may be technically less challenging but equally valuable for disease therapy. For instance, ex vivo genome editing in hematopoietic stem cells (HSCs) could potentially provide a cure for patients carrying sickle cell disease (SCD) and β-thalassaemia, 85 and targeted insertions via CRISPR strategies may provide a valuable alternative to T-cell engineering for cancer immunotherapy.…”
Section: Genome Editing For Disease Therapymentioning
confidence: 99%
“…A dual AAV approach codelivering the Staphylococcus aureus Cas9 and FIX-encoding transgenes has been used to correct hemophilia B in mice. 131 In this approach, the F9 transgene was targeted to exon 2 of the endogenous F9 locus. Intellia Therapeutics are testing codelivery of lipidnanoparticle encapsulated CRISPR/Cas9 components and an AAV containing a F9 transgene cDNA donor template in NHPs.…”
Section: Gene Therapymentioning
confidence: 99%
“…A gene-replacement strategy using CRISPR-Cas to integrate the transgene into the albumin locus downstream of the endogenous albumin promoter produced sustained FIX and FIIIV expression in hemophilia mouse models. 165,166 AAV8-Cas9 mediated integration of human FIX-padua exon 2-8 in exon 2 of mFIX and a codon-optimized FIIIV into intron 13 of albumin, and it developed persistent FIX or FIIIV levels for 7-8 months with no complications. 165,166 A similar strategy proved effective in the treatment of ornithine transcarbamylase (OTC) deficiency, an X-linked urea cycle disorder where a codon-optimized human OTC was inserted into the intron 4 of mouse OTC locus by using AAV8-SaCas9.…”
Section: Administrationmentioning
confidence: 99%
“…165,166 AAV8-Cas9 mediated integration of human FIX-padua exon 2-8 in exon 2 of mFIX and a codon-optimized FIIIV into intron 13 of albumin, and it developed persistent FIX or FIIIV levels for 7-8 months with no complications. 165,166 A similar strategy proved effective in the treatment of ornithine transcarbamylase (OTC) deficiency, an X-linked urea cycle disorder where a codon-optimized human OTC was inserted into the intron 4 of mouse OTC locus by using AAV8-SaCas9. 167 Conversely, Cas9-mediated HDR to correct the mutation had resulted in large deletions and affected endogenous OTC expression in the spf/ash heterozygous OTC mice.…”
Section: Administrationmentioning
confidence: 99%